Phytoremediation Activities of Indoor Plants: A Review - Lobo, Christopher B.; Narawade, Gauri N.; Kharade, Archana P.; Umap, Sayali B.; Dherange, Sayali H.; Shinde, Sanket P. (Microbiology and Biotechnology Research: An Overview Vol. 1, 2025)
Plants are commonly placed indoors to improve living and working spaces. Over the past 30 years, studies have demonstrated that indoor plants can significantly reduce most types of urban air pollution. Indoor plants purify the air from the harmful and toxic compounds present in it. Since ancient times, plants have been considered an auspicious symbol for many cultural and traditional purposes. Plants have also set their significance in human lives, not only biologically but also culturally. Plants have many beneficial activities like air purification, stress reduction, and improvement in cognitive power, and they exhibit many pharmacological activities too. Besides this, plants also add colors to the bland place, which makes the place more attractive and approachable. Plants that can thrive in partial shade/ indirect sunlight or full shade conditions can be listed under indoor plants. A sedentary lifestyle indoors has also had a great impact on human health. The closed and inadequately ventilated indoor spaces lead to Sick Building Syndrome (SBS), which is caused by particulate matter, like volatile organic compounds such as benzene, toluene, ethylbenzene, xylene, formaldehyde and polyaromatic hydrocarbons, as inorganic pollutants like O3, NO2, SO2, etc. and organic pollutants like CO2, CO, etc. that is released by the appliances and furniture present indoors. Plants absorb this particulate matter from the surroundings and convert it into energy required for their growth through photosynthesis. Plants help in mood elevation by providing fresh air and visual appeal. Phytoremediation deals with cost-effective environmental restoration by using plants to clean air, soil, and water. Various studies have proven that plants improve cognitive function by introducing them indoors. This review deals with the phytoremediating activities of various houseplants.